What's Fair in International Politics? Equity, Equality, and Foreign Policy Attitudes. (February 2022) - Powers, Kathleen E.; Kertzer, Joshua D.; Brooks, Deborah J.; Brooks, Stephen G.
How do concerns about fairness shape foreign policy preferences? In this article, we show that fairness has two faces—one concerning equity, the other concerning equality—and that taking both into account can shed light on the structure of important foreign policy debates. Fielding an original survey on a national sample of Americans, we show that different types of Americans think about fairness in different ways, and that these fairness concerns shape foreign policy preferences: individuals who emphasize equity are far more sensitive to concerns about burden sharing, are far less likely to support US involvement abroad when other countries aren't paying their fair share, and often support systematically different foreign policies than individuals who emphasize equality. As long as IR scholars focus only on the equality dimension of fairness, we miss much about how fairness concerns matter in world politics.